Does transparency pay off? Evidence from stock market segment switches - Moura, Luiz Carlos Feitosa de (2017)
Research on corporate governance has made a substantial effort to determine its impact on the stock market, albeit little attention has been given to testing the value of distinct listing segments of transparency. Building on the asymmetric information and investor awareness literatures, we test the relative importance of each level of corporate governance in the Brazilian Stock Exchange and how they are perceived among shareholders. Using an event study methodology, we provide clear evidence that investors are willing to reward high levels of transparency, although it is not the smartest investment choice in the short-term as one might expect. Finally, our last analysis explores situations in which the relationship between transparency and the firms’ cumulative abnormal returns can be enhanced. For this purpose, we make use of the Altman Z-score (2000) and present clear reasons of whether and how this strong relationship can be moderated. The results are robust to alternative event windows, different time-periods in the comparison, alternative sets of control variables, and distinct measures of financial health.